STUDI KOMPARATIF TARI JEPIN LEMBUT DESA SEKURA DAN DESA MENSERE - Yunita, Lili; Mering, Aloysius; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrac The purpose of this research is to analyze the similarity and the differences found in Jepin Lembut Dance In Sekura village and Mensere village. The method applied in this study is a comparative method with qualitative research forms. Data collection techniques adopted in this sdudy are observation, interview and documentation techniques. The techniques of data validity checking is in the form of observation and triangulation. The analytical techniques used are field analysis (reduction, display and conclusion) and the stages of data analysis (domain, taxonomic, compound and cultural theme). The result of the analysis of the composition elements are found in motion, theme, musical accompaniment, upper and lower design, make up and clothing, property, and venue.The differences of the lyric of the song and floor design. The similarity of body movement is the ngayak movement, base the step on leg movement and the tahtem exept the difference of hand movement. Song lyrics used are Arabic and one of floor pattern in Mensere and Sekura used Indonesian and eleven floor pattern. The results of this study can be used as reference material for teachers or educators and may serve as reference in cultural arts and skills lessons in school (especially dance subjects).Key words : Comparative Study, Jepin Lembut Dance